The Role Of Digital Literacy In Pai Learning In Improving The Quality Of Youth Worship - Roihan Arrosyid; Dzulfikar Akbar Romadlon (Institut Agama Islam An-Nawawi Purworejo, 2022)
This study aimed to determine the role of digital literacy in PAI learning in increasing student worship at home as an implementation of learning outcomes, as well as developing knowledge of Islamic Religious Education subjects. This study used a qualitative method, with the issue being students at SMP Negeri 2 Sedati, Sidoarjo Regency, namely grades 7 and 8, with a total of 46 early adolescents. Data collection through interviews, observation, and documentation through a google form questionnaire. The research results were analyzed using descriptive techniques. Based on research data, the results show that students can learn literate well in school literacy activities, are also active in discussions, and can implement worship with practical exercises. The Google form questionnaire indicates the increase in student worship by PAI teachers who show good grades. Digital literacy has a vital role in improving student worship at home. Students have the motivation to be diligent in prayer, one of which is because they get educational shows from gadgets, they can sort information so that it can be used as best as possible.